Investigation of PI3K-AKT and EMT-targeted miRNA profiles in palbociclib-treated Panc-1 and MiaPaCa-2 pancreatic cancer cells - Çoker Gürkan, Ajda; YERLİKAYA, PINAR OBAKAN; RENCÜZOĞULLARI, ÖZGE (My University, 2019)
The therapeutic strategies of pancreatic cancer (PC) are with the various combination treatment of anti-cancer drugs still in progress. However, the survival rate o f PC is still under 6%. because o f the limited therapeutics and no controllable prognosis. miRNAs have an important role in tire regulation of metabolic cascades which are critical in the differentiation of PC progression. In the current study, we aimed to investigate the role o f palbociclib (CDK4/6 inhibitor) on aberrantly activated pathways, PI3K/AKT, and EMT signaling axis through differently expressed miRNA profiles in Pane-1 and MiaPaCa-2 cells. The effect of palbociclib on cell viability was detennined by MTT cell viability test in time and dose-dependent maimer in PC cells. The expression profiles were analyzed by RT-PCR. We found that palbociclib effectively reduced cell viability and proliferation for following exposure of Panc-1 and MiaPaCa-2 cells for 24h. Additively, Panc-1 and MiaPaCa-2 cells were sensitive to palbociclib with the significant blockade in the G1 phase o f the cell cycle. Palbociclib decreased the expression o f PI3K and p-AKT in PC cells. Moreover, palbociclib downregulated the levels of B-catenin in Panc-1 cells, but not in MiaPaCa-2 cells. Palbociclib treatment led to increased levels of tumor suppressor miR- 506, miR-100, and miR-141 in MiaPaCa-2 cells, while the only detectable increase in tumor suppressor miRNA was detected formiR-100 levels in Panc-1 cells. Additionally, the oncomir miR-208 increased after palbociclib treatment in MiaPaCa-2 cells. In conclusion, palbociclib induced cell cycle arrest and reduced cell viability. However, palbociclib had a various effect on the regulation of PI3K/AKT and EMT signaling in each PC cell line. Investigating the effect of palbociclib on the tumor suppressor and oncomir miRNA profiles is a new therapeutic strategy to reduce cell viability and metastatic process of pancreatic cancer.